Pozycja Chin na międzynarodowym rynku broni - Skulski, Przemysław (Position of China in the International Weapon Market, 2008)
Presence of the People's Republic of China in the international weapon market has been observed for decades. However, important qualitative changes can be seen in recent years. Practically till the end of the 20th century China was perceived as the producer of low quality cheap weapons. The beginning of the 21st century brought important changes. The intensive development of the People's Republic of China involves improved technological potential of this country's economy. It is also visible in the armaments industry, which is capable of producing advanced constructions. China carries out intensive activities in the international weapons market, becoming an important competitor for the existing potentates (USA, France, Great Britain, Russia). At present, China seeks buyers mainly among developing countries but it can be assumed that they aim at reaching other countries in the future. Especially that modernization of the armament industry and expansion in the international weapon market are supported by major Chinese politicians, for whom they are elements of national security system and foreign policy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 223-236